Antimicrobial properties of cotton fabrics coated with silicone rubber/ZnO nanocomposites under the effect of UV irradiation. (23rd September 2022) - Hassan, Mahmoud S; Attia, Mona K; Attia, RM
In order to enhancement the antimicrobial properties and the thermal stability of the cotton fabrics for outdoor uses, they were coated with formulations of room-temperature vulcanizing silicone rubber (RTVSR)/synthesized zinc oxide nanoparticles (ZnO NPs). The coated fabrics were adjusted to different doses of ultraviolet (UV) irradiation, which act as a crosslinking factor to the silicone rubber, rather than as a photocatalytic agent for enhancing the antimicrobial activity of the ZnO NPs. The synthesized ZnO NPs were characterized by X-ray diffraction (XRD) and transmission electron microscopy (TEM); meanwhile, its impurity was examined using energy dispersive X-ray (EDS) analysis. The thermal stability and surface morphology of the coated fabrics were characterized by thermogravimetric analysis (TGA) and scanning electron microscopy (SEM). The results showed that the mechanical strength (MPa) of the coated fabrics was enhanced by ∼11% after UV irradiation for 120 min, accompanied by decrease in its swelling and solubility by ∼10 and 20%, respectively, as a result of UV crosslinking effect upon RTVSR. Meanwhile, the antimicrobial activity of the coated fabrics was enhanced by ∼50%, as a result of the photocatalytic effect of UV irradiation (120 min), at the constant percentage of 3% (ZnO NPs) in the coating formulations.